2013
DOI: 10.1103/physrevlett.111.040602
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Diffusive Transport in a Microscopically Integrable Hamiltonian System

Abstract: We demonstrate that a completely integrable classical mechanical model, namely the lattice Landau-Lifshitz classical spin chain, supports diffusive spin transport with a finite diffusion constant in the easy-axis regime, while in the easy-plane regime, it displays ballistic transport in the absence of any known relevant local or quasilocal constant of motion in the symmetry sector of the spin current. This surprising finding should open the way towards analytical computation of diffusion constants for integrab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
145
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(150 citation statements)
references
References 29 publications
5
145
0
Order By: Relevance
“…Specifically, studying dynamical correlations in quantum Heisenberg (XXX) chain of spins 1/2 at vanishing magnetization (or zero magnetic field), it has been demonstrated that the sole contribution to transport comes from the heat-peak with the sound-peaks being absent, but that the former broadens with a perfect KPZ scaling [9] over several orders of magnitude. This result is consistent with earlier observations [10] of z ∼ 1.5 in the integrable lattice Landau-Lifshitz (LLL) chain of classical spins [11] which can be thought of as an integrable classical version of the XXX model. More recently, these numerical experiments have been refined, confirming also the precise KPZ scaling profile of the heat-peak [12].…”
supporting
confidence: 93%
“…Specifically, studying dynamical correlations in quantum Heisenberg (XXX) chain of spins 1/2 at vanishing magnetization (or zero magnetic field), it has been demonstrated that the sole contribution to transport comes from the heat-peak with the sound-peaks being absent, but that the former broadens with a perfect KPZ scaling [9] over several orders of magnitude. This result is consistent with earlier observations [10] of z ∼ 1.5 in the integrable lattice Landau-Lifshitz (LLL) chain of classical spins [11] which can be thought of as an integrable classical version of the XXX model. More recently, these numerical experiments have been refined, confirming also the precise KPZ scaling profile of the heat-peak [12].…”
supporting
confidence: 93%
“…Intimately related to this question is the distinction between integrable and nonintegrable models. On the one hand, integrable models are characterized by a macroscopic number of (quasi)local conservation laws which can lead to anomalous thermalization [11,12] and ballistic transport [13][14][15]. As a consequence, diffusion is generally not expected to occur in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that a redundancy of description in the thermal states of isotropic integrable models, corresponding to the direction of the magnetization vector, gives rise to soft gauge modes at the level of hydrodynamics, which are decoupled from the quasiparticle sector and provide a channel for superdiffusive spin transport. We have further demonstrated that the dynamics of these modes reduces to a propagating torsional degree of freedom, whose coarsed-grained timeevolution is described by the stochastic Burgers equation, explaining the numerical observation of KPZ scaling in such models [16][17][18][19][20][21][22] .…”
mentioning
confidence: 99%